Digital Agriculture for Small-Scale Producers: Challenges and Opportunities - Chandra, Ranveer; Collis, Stewart (Communications of the ACM, 2021)
In this article, we discuss how digital technologies can benefit small-scale producers, smallholder farmers, and small livestock operators. We highlight how digital agriculture innovations must be developed differently for these users, and, consequently, the need for new approaches to make those innovations feasible for LMIC value chains. Investing in and focusing on the right technologies for smallholder farmers could have enormous impact at scale. We contend that the increased use of digital technologies can not only help address global food-production challenges, but also improve the livelihoods of millions of SSP households.